Environmental Factors and Children’s Malnutrition in Ethiopia - Silva, Patricia (World Bank, Washington, DC, 2012)
Ethiopia has one of the highest child malnutrition rates in the world. A considerable effort to monitor child malnutrition rates over the last two decades shows that, despite some improvements, approximately half of the children under five are still malnourished. Much of the burden of deaths resulting from malnutrition, estimated to be over half of childhood deaths in developing countries, can be attributed to just mild and moderate malnutrition. Several biological and social economic factors contribute to malnutrition. Using the 2000 Ethiopia Demographic and Health Survey data, this study examines the impact of access to basic environmental services, such as water and sanitation on the probability children are stunted and underweight. The focus is on the impact of externalities associated with access to these services. We find that biological factors, such as child's age and mother's height, and social economic factors, such as household wealth and mother's education, are important determinants of a child's nutritional status. This is consistent with the findings of most studies in this literature. With respect to the environmental factors, we find that there are indeed significant externalities associated with access to water and sanitation at the community level. The external impacts of community level of access to these services are an important determinant of the probability a child is underweight. Our results also show that the external impact of access to water is larger for children living in rural areas.